Contadores eletrônicos no laboratório didático. Parte II. Medida de intervalos de tempo sucessivos - Hessel, R. [UNESP]; de Oliveira, C. S. [UNESP]; Santarine, G. A. [UNESP]; Vollet, D. R. [UNESP]; Perinotto, A. C. [UNESP] (My University, 2008)
In this work we describe a procedure for measuring a series of time intervals in quick succession using several electronic counters connected to a single crystal oscillator used as a time standard. To illustrate the procedure, an application involving the conservation of linear momentum in a head-on collision between two gliders as they travel on a linear air track is discussed. In spite of the proposal to demand one counter for each time interval to be measured, instead of a single digital timer with memory, it is yet advantageous because the assembly cost of an electronic timer is very low compared to that of a commercial digital timer with memory appropriated for use in undergraduate laboratories. Copyright by the Sociedade Brasileira de Física.
Electronic counter in undergraduate laboratories: Part II. Measurement of successive time intervals
Keywords: Digital time with memory; Electronic counter; Measurement of successive time intervals; Operations in sequence